An Analysis of the Obligation to Review Archaeology Curriculum Based on Competency-Based Curriculum Approach - Mahsa Veisi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This study examines the reasons for the commitment to change in the Archaeology curriculum at all levels of its curriculum, not based on preferences but on the basis of competency-based curriculum models. The undergraduate and postgraduate courses in this field have not been reviewed for more than thirty years, and the PhD curriculum has been the same since its beginning. Today, in the world, curricula are shifting to skill-based, and many elements are being considered in formulating these programs. This study, considering the skills defined for archaeological graduates in the US Occupational Information Network (O * NET) as an index of the content analysis of archaeological educational competence in Iran, examines the relevance of this. The chapters deal with the skills. Its main purpose is to emphasize the need to review these courses based on a competency-based curriculum approach. The collection of data required in this study is library and documentary, and the method of data processing is descriptive and explanatory.